Receptor design and extraction of inorganic fluoride ion from aqueous medium - Das, Priyadip; Mandal, Amal Kumar; Kesharwani, Manoj K.; Suresh, Eringathodi; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2011)
A receptor with acidic methylene hydrogens is found to act as an efficient binding mode for F−. This reagent could as well be used for selective and quantitative extraction of F− from the aqueous solution of NaF and sea water.

Recognition of Hg2+ion through restricted imine isomerization: crystallographic evidence and imaging in live cells - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Suresh, E.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic Letters, 2012)
A newly synthesized imine-based receptor (L) showed remarkable specificity toward the Hg2+ ion in aqueous media over other metal ions. Coordination of L to Hg2+ induces a turn-on fluorescence response. This was explained based on the restricted imine isomerization along with PET on coordination to Hg2+. X-ray structural evidence tends to favor a C–C bond rotation rather than C═N isomerization for adopting a favorable conformation in L for coordination to Hg2+. This reagent could be used for imaging the accumulation of Hg2+ ions in HeLa cells.

Restricted conformational flexibility of a triphenylamine derivative on the formation of host-guest complexes with various macrocyclic hosts - Mandal, Amal Kumar; Suresh, Moorthy; Das, Priyadip; Das, Amitava (Chemistry a European Journal, 2012)
Herein, we report the host–guest-type complex formation between the host molecules cucurbit[7]uril (CB[7]), β-cyclodextrin (β-CD), and dibenzo[24]crown-8 ether (DB24C8) and a newly synthesized triphenylamine (TPA) derivative 1X3 as the guest component. The host–guest complex formation was studied in detail by using 1H NMR, 2D NOESY, UV/Vis fluorescence, and time-resolved emission spectroscopy. The chloride salt of the TPA derivative was used for recognition studies with CB[7] and β-CD in an aqueous medium. The restricted internal rotation of the guest molecule on complex formation with either of these two host molecules was reflected in the enhancement of the emission quantum yield and the average excited-state lifetime for the triphenylamine-based excited states. Studies with DB24C8 as the host molecule were performed in dichloromethane, a medium that maximizes the noncovalent interaction between the host and guest fragments. The Förster resonance energy transfer (FRET) process involving DB24C8 and 1(PF6)3, as the donor and acceptor fragments, respectively, was established by electrochemical, steady-state emission, and time-correlated single-photon counting studies.